A Cysteine-Rich Extracellular Protein Containing a PA14 Domain Mediates Quorum Sensing in Dictyostelium discoideum - Kolbinger, Alexandra (American Society for Microbiology, 2005)
Much remains to be understood about quorum-sensing factors that allow cells to sense their local density. Dictyostelium discoideum is a simple eukaryote that grows as single-celled amoebae and switches to multicellular development when food becomes limited. As the growing cells reach a high density, they begin expressing discoidin genes. The cells secrete an unknown factor, and at high cell densities the concomitant high levels of the factor induce discoidin expression. We report here the enrichment of discoidin-inducing complex (DIC), an ∼400-kDa protein complex that induces discoidin expression during growth and development. Two proteins in the DIC preparation, DicA1 and DicB, were identified by sequencing proteolytic digests. DicA1 and DicB were expressed in Escherichia coli and tested for their ability to induce discoidin during growth and development. Recombinant DicB was unable to induce discoidin expression, while recombinant DicA1 was able to induce discoidin expression. This suggests that DicA1 is an active component of DIC and indicates that posttranslational modification is dispensable for activity. DicA1 mRNA is expressed in vegetative and developing cells. The mature secreted form of DicA1 has a molecular mass of 80 kDa and has a 24-amino-acid cysteine-rich repeat that is similar to repeats in Dictyostelium proteins, such as the extracellular matrix protein ecmB/PstA, the prespore cell-inducing factor PSI, and the cyclic AMP phosphodiesterase inhibitor PDI. Together, the data suggest that DicA1 is a component of a secreted quorum-sensing signal regulating discoidin gene expression during Dictyostelium growth and development.